Clozapine rechallenge after neutropenia or leucopenia - Prokopez, Cintia R. (2016)
To rechallenge with clozapine for a patient who previously has experienced neutropenia or leucopenia or during clozapine treatment is a difficult clinical decision. Herein, we analyzed the results of such a rechallenge in 19 patients. We analyzed all the reports, from the database of the pharmacovigilance department of the Argentine National Administration of Drugs, Foods, and Medical Devices, of patients who were rechallenged with clozapine after a leucopenia or a neutropenia. Nineteen cases of rechallenge after leucopenia or neutropenia were reported between 1996 and 2014. One third of the patients re-exposed to clozapine developed a new hematologic adverse reaction. The second blood dyscrasia was less severe in 83% of the cases and had a shorter median latency as compared with the first (8 weeks vs 182 weeks, P = 0.0045). There were no significant differences for demographic and clinical characteristics of patients who developed a second dyscrasia as compared with those who did not. The present study shows that almost 70% of the patients rechallenged with clozapine after a leucopenia or a neutropenia did not develop a new hematological adverse effect, whereas the remaining 30% had a faster but less serious neutropenia.